Odpowiedzi

2010-02-26T15:55:09+01:00
5
a) (a+2)h =(7+2)1/3 = 9 x 1/3 =3
b) 4x:y(x+y)= 4 x 6 : -2(6-2) = 24 : -8= -3
c -x+2y-3 = 5+2 x -4 - 3 = 5-8-3 =-7
4
a)5-3x= 5-3 x -2 =5 +6 = 11
b)5-3 x 0.4 = 5- 3.2 =1.8
1 5 1
Najlepsza Odpowiedź!
2010-02-26T16:06:43+01:00
4.
a) 5-3x dla x=-2
5-3*(-2)
5-(-6)
5+6
11

5-3x dla x=0,4
5-3*0,4
5-1,2
3,8

5.
a)
(a+2)*h dla=7 i h=⅓
(7+2)*⅓
9*⅓
3

b)
4x:y(x+y) dla x=6 y=-2
4*6:{-2*(6+(-2)}
24:{-2*(6-2)}
24:{-2*4}
24:(-8)
-3

c)
-x+2y-3 dla x=-5 y=-4
-(-5)+2*(-4)-3
5-8-3
-6
1 5 1